Mitochondrial DNA analysis of medieval sheep (Ovis aries) in central Italy reveals the predominance of haplogroup B already in the Middle Ages. (June 2015) - Gabbianelli, F.; Gargani, M.; Pariset, L.; Mariotti, M.; Alhaique, F.; De Minicis, E.; Barelli, L.; Ciammetti, E.; Redi, F.; Valentini, A.
Summary We retrieved 34 medieval ovicaprine remains, from three archaeological sites of central Italy dating to about 1000 years old, and analyzed them using mitochondrial DNA. We compared the reconstructed haplogroups with modern sheep samples from Europe and the Middle East and sequences from the literature. In modern sheep, haplogroup HA is present in countries with access to the Mediterranean and close to the domestication center, whereas it is very rare or absent in the rest of Europe. The haplogroup HB was predominant in ancient samples (90%), whereas haplogroup HA was found at 10%. Ancient haplogroups match the present distribution in modern sheep in Italy, indicating that the current proportion of HA/HB was already established in the Middle Ages and is not the result of subsequent events such as selective breeding practices.